2015
DOI: 10.1017/jfm.2015.247
|View full text |Cite
|
Sign up to set email alerts
|

On the reflection and transmission of circumferential waves through nozzles

Abstract: This paper presents a mathematical model for predicting the propagation of circumferential waves (acoustic, entropy and vorticity waves) through an annular nozzle. Combustion chambers in modern aero-engines are typically annular, and so a model for circumferential waves is essential for understanding and predicting both combustion noise and thermoacoustic instabilities for such geometries. The linearised Euler equations are solved using the Magnus expansion to obtain the reflection and transmission coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Many low order analytical models for entropy noise have been developed, e.g., [2, 1215]. Analytical, experimental and numerical analyses have suggested that for typical gas turbine accelerations (from low subsonic flow to approximately sonic flow), entropy noise may greatly exceed the “direct combustion noise” generated by flame volume expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Many low order analytical models for entropy noise have been developed, e.g., [2, 1215]. Analytical, experimental and numerical analyses have suggested that for typical gas turbine accelerations (from low subsonic flow to approximately sonic flow), entropy noise may greatly exceed the “direct combustion noise” generated by flame volume expansion.…”
Section: Introductionmentioning
confidence: 99%
“…For non-compact choked nozzles with a supersonic diffuser [24] and for subcritical non-compact nozzles [25], the linear transfer functions have been calculated numerically and analytically for the upstream and downstream acoustic waves generated by an incident entropy disturbance. Duran & Morgans [26] studied numerically using high resolution 1-D and 2-D computations the propagation of circumferential waves (acoustic, entropy and vorticity waves) through an annular non-compact nozzle with isentropic mean flow throughout the divergent section of the nozzle (i.e. with no shocks).…”
Section: Introductionmentioning
confidence: 99%
“…Physically speaking, if the combustor's outlet is choked, these three types of perturbations interact, the reflected pressure perturbation will be excited by the vortical and entropic perturbations. The corresponding boundary condition can be found in Duran and Morgans [27]. As we are interested in the analysis of intrinsic thermoacoustic oscillation, we only consider the acoustic feedback mechanism.…”
Section: Comparison With Literature Resultsmentioning
confidence: 99%